Nebrija y Maquiavelo ante un epigrama de Ausonio: paratexto y texto - Barbolani, Cristina (Cuadernos de Filología Italiana, 2007)
This article analyses the presence of an epigram by the poet Ausonio (IV AD) in Nebrija and in Machiavelli. The text by Ausonio, which in turn derived from a Greek text by Posidipo (III BC), must have been familiar to the European Humanism, since it spread the traditional representation of the figure of Chance bald and with a lock on her forehead, sometimes accompanied by her complementary Poenitentia until it was deeply rooted in the collective imagery in the Renaissance; in fact, it appears like that in the Emblem CXXI by Alciato and in authors such as Boiardo and Ariosto. The Spanish philologist Nebrija reproduced this late Latin epigram in the dedication to the archbishop Fonseca in his Libri minores (paratextual function); however Machiavelli translated it and transformed it significantly in his brief chapter Dell’Occasione. Therefore, this text appeared in Nebrija for the profit of a didactic principle characteristic of his erudite humanism, while Machiavelli’s translation led to a new interpretation which spread his dynamic and pessimistic concept of reality